Low Mitochondrial DNA Copy Number is Associated With Adverse Clinical Outcomes in Peritoneal Dialysis Patients. Issue 7 (February 2016) - Yoon, Chang-Yun; Park, Jung Tak; Kee, Youn Kyung; Han, Seung Gyu; Han, In Mee; Kwon, Young Eun; Park, Kyoung Sook; Lee, Mi Jung; Han, Seung Hyeok; Kang, Shin-Wook; Yoo, Tae-Hyun
Abstract : Abstract: Mitochondrial dysfunction may play an important role in abnormal glucose metabolism and systemic inflammation. We aimed to investigate the relationship between mitochondrial DNA (mtDNA) copy number and clinical outcomes in peritoneal dialysis (PD) patients. We recruited 120 prevalent PD patients and determined mtDNA copy number by PCR. Primary outcome was all-cause mortality, whereas secondary outcomes included cardiovascular events, technical PD failure, and incident malignancy. Cox proportional hazards analysis determined the independent association of mtDNA copy number with outcomes. The mean patient age was 52.3 years; 42.5% were men. The mean log mtDNA copy number was 3.30 ± 0.50. During a follow-up period of 35.4 ± 19.3 months, all-cause mortality and secondary outcomes were observed in 20.0% and 59.2% of patients, respectively. Secondary outcomes were significantly lower in the highest mtDNA copy number group than in the lower groups. In multiple Cox analysis, the mtDNA copy number was not associated with all-cause mortality (lower two vs highest tertile: hazard ratio [HR] = 1.208, 95% confidence interval [CI] = 0.477–3.061). However, the highest tertile group was significantly associated with lower incidences of secondary outcomes (lower two vs highest tertile: HR [95% CI] = 0.494 [0.277–0.882]) after adjusting for confounding factors. The decreased mtDNA copy number was significantly associated with adverse clinical outcomes in PD patients. Abstract : Supplemental Digital Content is available in the text